Optimalisasi Pemahaman Siswa terhadap Materi Sistem Pernapasan melalui Media Poster Interaktif Berbasis Canva Pada Siswa SMP Muhammadiyah 1 Surabaya - rendi, muhammad (Universitas Muhammadiyah Surabaya, 2024)
This research aims to improve students' understanding of respiratory system material through the use of Canva-based interactive poster media. The method used is Classroom Action Research (PTK) with the Kemmis and McTaggart model which consists of four stages: planning, action, observation, and reflection. The subject of the study was a grade VIII student of SMP Muhammadiyah 1 Surabaya. The results showed that the use of Canva-based posters significantly showed an average increase in comprehension by 20 points or 33.3% and an average increase in learning outcomes of 15 points or 21.4% indicating that PTK could significantly improve the quality of learning. The study also identified several constraints, such as device and time limitations. This obstacle is overcome through intensive guidance and more flexible timing. Overall, the results of this study show that Canva-based poster media is effective in improving students' understanding, their engagement in learning, and motivation to learn. These findings support the use of digital-based media as an innovative solution in science learning.